Elevated gliadin antibody levels in individuals with schizophrenia. (September 2013) - Okusaga, Olaoluwa; Yolken, Robert H.; Langenberg, Patricia; Sleemi, Aamar; Kelly, Deanna L.; Vaswani, Dipika; Giegling, Ina; Hartmann, Annette M.; Konte, Bettina; Friedl, MARION; Mohyuddin, Farooq; Groer, Maureen W.; et al.
Abstract: Objectives. We aimed to replicate, in a larger sample and in a different geographical location, the previously reported elevation of anti-gliadin IgG antibodies in schizophrenia. Methods. A total of 950 adults with schizophrenia (severity assessed by PANSS) and 1000 healthy controls were recruited in the Munich metropolitan area. Anti-gliadin IgG antibodies were analyzed with ELISA. χ 2 -tests and logistic regression were used to analyze the association of schizophrenia with elevated anti-gliadin IgG. A multivariable general linear model was used to compare anti-gliadin IgG levels between patients and controls. Results. The odds ratio of having elevated anti-gliadin IgG antibodies in the schizophrenia group was 2.13 (95% CI 1.57 to 2.91, p < 0.0001). Mean anti-gliadin IgG levels were higher in schizophrenia patients (0.81 ± 0.79 vs. 0.52 ± 0.56, t = 9.529, df = 1, 697, p < 0.0001) and the difference persisted after adjusting for potential confounders. Conclusions. Our study, limited by its cross sectional design, confirmed an association between anti-gliadin IgG antibodies and schizophrenia. Replication in longitudinal studies, clinical trials of gluten free diet and mechanistic investigation could lead to novel treatment targets, preventive and therapeutic considerations in schizophrenia.